Revision of European Brachysira species (Brachysiraceae, Bacillariophyta): III. Species formerly included in the Brachysira serians-complex. Issue 1 (2nd January 2022) - Van de Vijver, Bart; Schuster, Tanja M.; Kusber, Wolf-Henning; Kennedy, Bryan; Hamilton, Paul B.; Albert, Raino-Lars; Ballings, Petra; Wetzel, Carlos E.; Ector, Luc
ABSTRACT: This third paper revising the European Brachysira species deals with Brachysira serians and the closely related B. brebissonii–intermedia complex. The morphology of these species is characterised in greater detail than before based on a combination of analyses of original type material and additional historic and modern samples. All taxa in this complex are typically found in oligotrophic, acidic environments. The largest species in this complex are B. serians and B. wygaschii, which both possess a distinct Voigt discordance. Although they often co-occur, differences in their valve outline and dimensions are distinctive. The type material of Brachysira brebissonii is restudied and differs from a widespread use of this species name in Europe. As a result, Anomoeoneis intermedia, described from Denmark, is considered a more recent heterotypic synonym of B. brebissonii . Two new species are described to clarify the taxonomic identity of the B. brebissonii–intermedia species complex: B. elisabethiana Van de Vijver, C.E.Wetzel & Ector, sp. nov. and B. confusa Van de Vijver, R.L.Albert, B.Kennedy & Kusber, sp. nov. The type material of the morphologically similar B. arctoborealis from North America is studied for comparison. The ecological preferences of all the reported taxa are derived from the accompanying diatom flora in the investigated samples.